Radiographic and clinical comparison of immediate and non immediate loading of single tooth implants / Wesam Seddik Turki - Alturki, Wesam (2006)
Purpose: The aim of this study was to determine if these is a difference in success rate and crest bone changes between immediate loading and delayed loading groups of single tooth implants. Material and Method: The study was focused on clinical assessment of implant mobility and radiographic analysis of changes in crest bone level. Patients were divided into 2 groups (Immediate Loading Group- all implants loaded within 48 hours) and (Delayed Loading Group- all implant loaded after 4 months). All implants were placed by single a surgeon. Change of bone level around implants were measured on periapical radiographies using paralleling technique standardized with individual occlusal bite index. All radiographs were digitized with high resolution using flatted scanner and computer program (Leica). The crest bone position relative to the implant reference point (Implant abutment interface) at mesial and distal side was evaluated at implant placement. at abutment placement and 4 month later. The measurement of bone level was adjusted according to the magnification. Result : The Immediate loading group consisted of 11 patient with 15 implants Delay loading group consisted of 1O patient with15 implants. In both group there were 2 mobile implants; one implants in each group. The remaining 28 implants were stable with no pain and no inflammation. The success rate in both group was 93%. In radiographic analysis there was no statistically significant different in bone loss between 2 groups (p>. 05)the mean marginal bone loss was 0.3 in immediate loading group and 0.4 in delayed loading group. Conclusion: The outcome of this study showed high success rate of implant survival and no significant difference in implant stability and radiographic marginal bone loss between immediate loading and delayed loading groups in un splinted single tooth implants. Immediate loading single implants appear to be techniques that can provide satisfactory implant success rate in selected cases.